Analisis Konsep Khilafah dalam Al Qur’an dan Sejarah - Suryani, Irma; Afrizal, Afrizal; Syawaluddin, Syawaluddin (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The reconstruction of the caliphate system has become a topic of debate among various Muslim communities, inspired by the past glory of Islam under this system. However, differing views on the concept of the caliphate have hindered reconstruction efforts. This study aims to explore the legal basis of the caliphate in the Qur'an and Islamic history using the maqâṣidi interpretation method and historical analysis. The findings reveal that the term "caliphate" is not explicitly mentioned in the Qur'an. Terms such as "khalâif," "khulafâ," and "khalîfah" more closely refer to the regeneration of communities or individuals as leaders without emphasizing a specific form of government. Moreover, the history of the caliphate indicates that the system lacks a standardized format that could serve as a model in the modern era. The researchers conclude that the caliphate is not the only way to uphold Islamic law; other forms of government that align with the context of the times can also be viable options.